The Project Management Ontology called ProjectCO: Architectural Aspects, Concepts, and Usefulness - Olsina, Luis; Becker, Pablo; Papa, María Fernanda (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE), 2024)
This paper presents the concepts, relationships, constraints, and verification issues of the project management ontology called ProjectCO. Its concepts represent key concerns of the conceived world for project management, embracing particular things (or entities) and their relations, as well as assertions that deal with them. ProjectCO is placed at the core level in the context of a five-tier ontological architecture, which considers foundational, core, top-domain, low-domain, and instance layers. A given ontology is located in this architecture according to the level of generality/specificity of its concepts, which in turn depend on the established development goal and scope. Therefore, since we aim for ProjectCO concepts to be cross-cutting, domain-independent concerns of any specific discipline, its scope is limited to core terms that need to be reused and specialized at lower domain levels. Note that many definitions and labels of ProjectCO terms were adopted or adapted from four well-known standard glossaries, as well as from a previous project management ontology. To showcase its usefulness, this work discusses enriched and harmonized concepts for a top-domain ontology for measurement and evaluation projects.